1976
DOI: 10.1016/0040-6031(76)85004-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of lead titanyl oxalate tetrahydrate

Abstract: The thermal behaviour of PbTiO(C20&-4H20(PTO) has been investigated, employing TG, quantitative DTA, infrared spectroscopy and (high temperature) X-ray powder diffraction.The decomposition involves four main steps. The first is the dehydration of the tetrahydrate (30-lSO'C), followed by a small endothermic (27&31O@C) and a large exothermic decomposition of the oxalate. The main (exothermic) oxalate decomposition (310-390°C) rest&s in a stable oxide-carbonate PbTiOz_s(C03)o_s. In the last step a phase transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Barium titanate product is formed by calcination and firing of the precursor obtained from the wet chemical methods. While there have been many studies of the decomposition behavior of precursors reported (Swilam et al, 1973;Gallagher and Thomson, 1965;van de Velde and Oranje, 1976;Chaput and Boilot, 1990), there have not been any quantitative and kinetic investigations carried out because of the complicated reaction routes and numerous intermediates in-volved in the formation of barium titanate in the calcination step.…”
Section: Introductionmentioning
confidence: 99%
“…Barium titanate product is formed by calcination and firing of the precursor obtained from the wet chemical methods. While there have been many studies of the decomposition behavior of precursors reported (Swilam et al, 1973;Gallagher and Thomson, 1965;van de Velde and Oranje, 1976;Chaput and Boilot, 1990), there have not been any quantitative and kinetic investigations carried out because of the complicated reaction routes and numerous intermediates in-volved in the formation of barium titanate in the calcination step.…”
Section: Introductionmentioning
confidence: 99%